FAKTOR SOSIAL YANG BERHUBUNGAN DENGAN EFEKTIFITAS PENGEMBALIAN BANTUAN PENGUATAN MODAL PROYEK PENGEMBANGAN KETAHANAN PANGAN (PPKP) DI KABUPATEN LAMPUNG TENGAH DAN KOTA METRO - Gultom, Dame Trully (Indonesian Journal of Socio Economics)
The objectives of the research were to study (1) the effectiveness capital  strengthening aid return of PPKP, (2) the correlation between farmer motivation and the effectiveness capital strengthening  aid return of PPKP, (3) the correlation between the extension worker role  and the effectiveness capital strengthening  aid return of PPKP, (4) the correlation between farmer knowledge and the effectiveness capital strengthening  aid return of PPKP.  The research was conducted using survey method in Margorejo Village  South Metro  Sub District Metro District and Bangun Rejo Village Gunung Sugih Sub District Central Lampung District. The research samples were 58 farmers from Margorejo Village and 68 farmers from Bangun Rejo Village.  They  were proportionately randomly selected with 10% precision from the population. The data collected were analyzed descriptively and statistically using Rank Spearman correlation.  The study showed that: (1)  farmers were effective returning aid of PPKP, (2)  there was correlation between farmer motivation and the effectiveness of repayment of PPKP in Metro District, but not in Central Lampung District, (3) there was no correlation between the role of extension worker role and the effectiveness of repayment of PPKP in both Metro and Central Lampung Districts, (4) there was correlation between farmer knowledge and the effectiveness repayment of PPKP in both Metro and Central Lampung Districts.